Gemcitabine Plus Docetaxel, Dacarbazine, Doxorubicin Combinations, or Doxorubicin Alone as First-Line Treatment for Advanced/Metastatic Leiomyosarcoma: A Retrospective Analysis at a Sarcoma Center - Ted Kim; Clara Hao; Minggui Pan; Kristen N. Ganjoo; Nam Q. Bui (Diseases)
Background/Objectives: Locally advanced and metastatic leiomyosarcoma (LMS) is an aggressive cancer with limited treatment options. This single-institution, retrospective study evaluated the efficacy of first-line chemotherapy regimens in patients with advanced or metastatic LMS treated at Stanford Medical Center. Methods: Seventy-four patients with unresectable or metastatic LMS were deemed eligible and treated with first-line chemotherapy regimens, including gemcitabine plus docetaxel, dacarbazine, doxorubicin combinations (with evofosfamide or ifosfamide), and doxorubicin monotherapy. Progression-free survival (PFS), overall survival (OS), and disease control rate (DCR) were assessed using RECIST v1.1, with survival analyses performed using Kaplan–Meier and Cox proportional hazards methods. Results: The cohort consisted of 56 females (75.7%) and 18 males (24.3%), with a median age of 55.5 years. The majority (93.2%) had metastatic disease. The median PFS for the entire cohort was 4.9 months (range: 0.6–28.1 mo), and the median OS was 27.3 months (range: 1.9–140.2 mo). The doxorubicin combination (DC) group had the highest median PFS of 7.9 months (range: 0.6–15.8 mo). Doxorubicin alone had the highest median OS of 33.8 months (4.2–100.2 mo). Doxorubicin combinations demonstrated superior PFS in both uterine and non-uterine LMS subgroups. Conclusions: These findings reaffirm the efficacy of doxorubicin-based combination regimens as a first-line treatment for locally advanced and metastatic LMS, particularly in non-uterine LMS.